Promoting equity in study abroad: A focus on first-generation and students of color in the USA - Tracy-Ventura , Nicole; Washington, Adrienne Ronee; Mikheeva, Iuliia (Studies in Second Language Learning and Teaching, 2024)
Education abroad is considered a high-impact practice with short-term benefits such as intellectual development and higher retention and university graduation rates, along with more long-term benefits such as personal and professional development. Thus, it is important to ensure that all students have an equal opportunity to study abroad; however, research shows that this is not the case. For example, in the United States, the majority of study abroad participants are white (68% according to Institute of International Education [IIE], 2022), and the racial and ethnic diversity of study abroad participants is well below the percentage of undergraduate students of color overall. First-generation college students also make up a small proportion of the students who study abroad, with some coming from racial and ethnic minoritized backgrounds as well. This lack of diversity in study abroad should be a major concern for institutions of higher education. To address this issue at our own university, we surveyed 137 first-generation and students of color to gather data on their interests, opinions, and reservations about study abroad. Results demonstrate that they are overwhelmingly positive about study abroad but are concerned about cost, fitting it into their degree plan, and not knowing languages other than English. Additionally, 81% reported that they did not know where to start or how to get involved in study abroad. These results suggest that a more equity-minded approach with targeted interventions is needed to increase study abroad participation among first-generation and students of color.